2006
DOI: 10.1007/bf03022251
|View full text |Cite
|
Sign up to set email alerts
|

Massive transfusion and coagulopathy: pathophysiology and implications for clinical management

Abstract: Purpose:To review the pathophysiology of coagulopathy in massively transfused, adult and previously hemostatically competent patients in both elective surgical and trauma settings, and to recommend the most appropriate treatment strategies. Methods:Medline was searched for articles on "massive transfusion," "transfusion," "trauma," "surgery," "coagulopathy" and "hemostatic defects." A group of experts reviewed the findings. Principal findings:Coagulopathy will result from hemodilution, hypothermia, the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
108
0
15

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(125 citation statements)
references
References 113 publications
(104 reference statements)
0
108
0
15
Order By: Relevance
“…Its origin is multicausal, and the main etiologic factors are hypothermia, fibrinolysis activated by tissular trauma and by endothelial damage, and dilution of coagulation factors and platelets [86][87][88][89][90][91]. Occasionally, a traumatized patient has a pre-existing condition such as liver or hematologic diseases or anticoagulant treatment that can predispose to bleeding [92], and must be identified in the anamnesis.…”
Section: Transfusion Threshold and Coagulopathy Correctionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its origin is multicausal, and the main etiologic factors are hypothermia, fibrinolysis activated by tissular trauma and by endothelial damage, and dilution of coagulation factors and platelets [86][87][88][89][90][91]. Occasionally, a traumatized patient has a pre-existing condition such as liver or hematologic diseases or anticoagulant treatment that can predispose to bleeding [92], and must be identified in the anamnesis.…”
Section: Transfusion Threshold and Coagulopathy Correctionmentioning
confidence: 99%
“…The characterization of coagulopathy is made in most of the cases by simple laboratory tests: platelet count, activated partial thromboplastin time, prothrombin time-international normalized ratio, and fibrinogen concentration, which guide the administration of fresh frozen plasma, platelets, and cryoprecipitate [87][88][89][90][91]. Damage control surgery is a powerful ancillary tool in the coagulopathic patient who is being operated on.…”
Section: Transfusion Threshold and Coagulopathy Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Often, the results of routine hemostatic tests are generally available with a delay of at least 30-60 min; results, therefore, may not be able to provide an accurate picture of the current hemostatic physiology [22]. Hardy et al [23] concluded that bedside monitors of hemostasis are needed urgently for the management of operative and trauma-associated bleeding [10][11][12][13][14][15][16][17][18][19]. The bedside tests for PT and aPTT in whole blood using the CoaguCheck (Roche Diagnostics, Switzerland) attempted to overcome this limitation.…”
Section: Limitations Of Historical Coagulation Testingmentioning
confidence: 99%
“…Massive transfusion has been defined loosely as the replacement of one blood volume in a 24-hr period. 6 Although, a more dynamic definition of massive transfusion includes the transfusion of at least four red cell concentrates within one hour and an ongoing need for blood replacement in the foreseeable future. 6 The management of a massively bleeding patient is complex and is aimed at concurrent hemorrhage control and blood volume replacement.…”
Section: Summary Reviewmentioning
confidence: 99%